Edukasi Mengenai Peranan Reaksi Kimia dalam Tubuh Bagi Anak Usia Dini di Kober Al-Mujahidin - Estin Nofiyanti; Noer Laelly BTAG; Nandhini Huda A; Gatut Ari Wardani (Universitas Mathla'ul Anwar Banten, 2022)
THE ROLE OF CHEMICAL REACTION IN THE BODY EDUCATION FOR EARLY CHILDHOOD IN KOBER AL-MUJAHIDIN. The essence of Early Childhood Education (PAUD) is education that organized with the aim of facilitating the growth and development of children as a whole, emphasizing on the development of all aspects of the child's personality. The PAUD program must focus on all aspects of child development according to the interests, needs, and abilities of the child. In addition, development programs should instill and foster behavior and attitude development through good habits. Science learning can be used as a medium to stimulate developmental aspects and maximize children's potential. This Community Service Program was held at Kober Al Mujahidin, Pangandaran Regency. This activity aims to introduce body organs and provide education about the role of chemical reactions in the body for early childhood. This community Service Program was carried out through three stages, namely the preparation stage (survey & observation), implementation and evaluation stages. The results showed that the implementation program can increase students' understanding in recognizing the chemical processes that occur in their bodies. School partners also gain experience contextual learning materials for early childhood students in an interactive and fun way.